Targeted Gene Sequencing in Children with Crohn's Disease and Their Parents: Implications for Missing Heritability. Issue 9 (1st September 2018) - Chen, Jiun-Sheng; Hu, Fulan; Kugathasan, Subra; Jorde, Lynn B; Nix, David; Rutherford, Ann; Denson, Lee; Watkins, W Scott; Prahalad, Sampath; Huff, Chad; Guthery, Stephen L
Abstract: Crohn's disease is a complex genetic trait characterized by chronic relapsing intestinal inflammation. Genome wide association studies (GWAS) have identified more than 170 loci associated with the disease, accounting for ∼14% of the disease variance. We hypothesized that rare genetic variation in GWAS positional candidates also contribute to disease pathogenesis. We performed targeted, massively-parallel sequencing of 101 genes in 205 children with Crohn's disease, including 179 parent-child trios and 200 controls, both of European ancestry. We used the gene burden test implemented in VAAST and estimated effect sizes using logistic regression and meta-analyses. We identified three genes with nominally significant p-values: NOD2, RTKN2, and MGAT3 . Only NOD2 was significant after correcting for multiple comparisons. We identified eight novel rare variants in NOD2 that are likely disease-associated. Incorporation of rare variation and compound heterozygosity nominally increased the proportion of variance explained from 0.074 to 0.089. We estimated the population attributable risk and total heritability of variation in NOD2 to be 32.9% and 3.4%, respectively, with 3.7% and 0.25% accounted for by rare putatively functional variants. Sequencing probands (as opposed to genotyping) to identify rare variants and incorporating phase by sequencing parents can recover a portion of the missing heritability of Crohn's disease.